Mengungkap Karakteristik Belajar Peserta Didik - Hamdah Hanyfah; Khurun In Kamila; Siti Rahmatur Riskiyah; M Yunus Abu Bakar (JOURNAL SAINS STUDENT RESEARCH, 2025)
The learning characteristics of students play a crucial role in determining the success of the learning process in the classroom. Each student has different learning styles, interests, and tendencies, which affect how they absorb information and interact with the learning material. This study aims to reveal various learning characteristics of students that can influence the effectiveness of learning. By understanding these characteristics, educators can design teaching strategies that are more aligned with the individual needs of students, creating an environment that supports their academic and personal development. This abstract will discuss the key factors that shape students' learning characteristics and their implications for improving educational quality.